Hyperbranched polymers tune the physicochemical, mechanical, and biomedical properties of alginate hydrogels. (March 2022) - Mathew, M.; Rad, M.A.; Mata, J.P.; Mahmodi, H.; Kabakova, I.V.; Raston, C.L.; Tang, Y.; Tipper, J.L.; Tavakoli, J.
Abstract: The current research aimed to fabricate an alginate-hyperbranched polymer (HBP) complex, using a vortex fluidic device (VFD), to control the physicochemical, structural, and mechanical properties of alginate hydrogel; thus, providing a dominant biomaterial system for different biomedical applications. Samples were prepared by mixing alginate (6%w/w) with HBP (0.85 μM) before cross-linking with Ca 2+ (100 mM). Magnet stirrer (600 rpm) and VFD (6000 rpm) were used to prepare experimental samples, and alginate was used as control. Comprehensive evaluations of bulk and surface morphology, microstructural analysis, swelling kinetics, mechanical characteristics, cytotoxicity, and formation of hydrogen bonds were conducted. The findings from this study revealed that the addition of HBP to alginate structure led to a higher swelling capability (86%), increased diffusion coefficient (66-fold), and enhanced failure mechanical properties (160% and 20% increases for failure stress and elongation at break, respectively) than control. Traditional mixing affected the surface morphology, while the bulk structure remained unchanged. Moreover, the rate of degradation was not significantly different between alginate and alginate-HBP samples. When VFD was incorporated, a higher swelling ratio (30%) was observed than the control sample and the coefficient of diffusion increased (34-fold). The associated degradation rate increased 30-fold, and the failure stress and elongation at break were increased 310% and 83%, respectively, compared to the control sample. The micromixing of alginate with HBP under high shear stress using a VFD created a micro-hybrid composite formed by alginate microparticles embedded in an alginate sheet. Graphical abstract: Image 1 Highlights: Hyperbranched polymer (HBP) altered the physicomechanical and structural properties of alginate hydrogel. The addition of HBP to alginate hydrogel enhanced swelling and mechanical properties. The microstructure of alginate-HBP was tuned under submicron high shear stress mixing. The degradation property of alginate hydrogel was modified by HBP.